A bibliometric examination and state-of-the-art overview of hydrogen generation from photoelectrochemical water splitting - Nabgan, Walid; Nabgan, Bahador; Jalil, Aishah Abdul; Ikram, Muhammad; Hussain, Ijaz; Bahari, Mahadi B.; Tran, T.V.; Alhassan, Mansur; Owgi, A.H.K.; Parashuram, L.; Nordin, Abu Hassan; Medina, Francisco (International journal of hydrogen energy, 2024)
Renewable energies can reduce emissions from fossil fuel-based power production by a significant amount, reducing climate change. Among the several options being investigated, hydrogen is now recognized as one of the primary enabling technologies for future large-scale and long-term green storage of renewable energy. However, using clean and renewable energy sources like water and sunlight is the best option. According to recent studies, photoelectrochemical (PEC) water splitting is a potential technology for creating hydrogen using free solar energy since hydrogen and oxygen gases may be easily identified in PEC. This study uses bibliometric and systematic literature review methodologies to examine the scientific understanding of PEC water splitting and hydrogen generation, evaluating 936 articles issued in the Web of Science database from 1970 to 2022. The authors looked at how PEC water splitting research has developed compared to prior research, what criteria make up practical approaches, and what subjects have emerged as new trends in reacting to changing situations. The key findings from the article analysis, future research potential, and practical implications for the field are discussed. [Display omitted] •A bibliometric analysis of photoelectrochemical and hydrogen production is conducted.•Web of Science database from 1970 to 2022 was used in this review.•The key findings from the article analysis are discussed.•Future research potential and practical implications for the field of study are explored.